PROGRAM KREATIVITAS MAHASISWA PERMEN HERBAL “MPON SEHAT” - Febrizka Nabilla; Nadya Berliana Putri; Putri Dwi Rizni Ananda; Dini Safitri (Universitas Sanata Dharma, 2020)
Since the pandemic outbreak until now, no drugs and vaccines have been found to fight the COVID-19 pandemic. Therefore, one of the alternatives to fight covid 19 virus is to maintain health and increase endurance despite intense activity. With the condition of Indonesia that is being exposed to the COVID-19 virus outbreak, we made a breakthrough to encourage the public to maintain and increase endurance. In order not to be susceptible to various viruses and keep healthy, consuming herbal medicine is one among the many ways. Mpon Sehat is a new breakthrough made from the basic ingredients of herbal medicine that is made into sweets with a sweet taste. Mpon is very beneficial for the body, for it can increase endurance and nourish the body. The purpose of making this candy is to provide a solution for people who are busy and do not have time to consume herbal medicines.This herbal candy can also be used as an alternative for some people who don't like herbal medicine but want to feed the body. This candy is not bitter or spicy like other spices, but it tastes sweet and tastes like an unwanted spice. It has other uniqueness such as chewy texture, unique packaging- consisting of 2 colors and easy to carry anywhere. In this service, using the method of implementing community service on April 15, 2020 starting at 15:00 until 17:00 in Bintaro, it is done face to face with the target audience by distributing products for free and doing image branding.As a result of this creativity program, we received satisfying opinions and criticisms and suggestions from the target audience to develop products and improve existing deficiencies. Then we made a video about the results of the creativity program and posted it on Instagram. In addition we also share information about the importance of maintaining health by consuming herbal medicines through social media such as Instagram. Instagram can facilitate the promotion of the products with a broad reach and is intended for everyone.